Logic Gates and Introduction to Computer Architecture - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
The basic components of an Integrated Circuit (IC) is logic gates which made of transistors, in digital system there are three basic logic operations and they are called AND, OR and NOT.
Citation Key Alias: lens.org/102-318-987-004-411
Keywords: dept.csc